2023
DOI: 10.7343/as-2023-628
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mapping of potential recharge in the Middle Seybouse sub-catchment of the Guelma region (North East of Algeria): contribution of remote sensing, multi-criteria analysis, ROC-Curve and GIS

Abstract: Due to the rapid population increase in the Middle Seybouse sub-catchment area in North-East Algeria, the intense agricultural practices, and the industrial development, precious water resources proven to be significantly challenged in their sustainable exploitation both in terms of quantity and quality. The aim of this study is to identify the most suitable areas for groundwater recharge in the Middle Seybouse sub-catchment, over about 770.91 km², using remote sensing data and Geographical Information Systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…More particularly the zone where the deposit is located given the compactness of the gray to beige limestone rock which does not allow the infiltration of rainwater in depth, hence the non-existence of sources of outlets on the flanks and at the foot of the deposit. The rocky massif of the bouzitoune quarry, is part of the north-eastern massifs of the Constantine neritic series [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…More particularly the zone where the deposit is located given the compactness of the gray to beige limestone rock which does not allow the infiltration of rainwater in depth, hence the non-existence of sources of outlets on the flanks and at the foot of the deposit. The rocky massif of the bouzitoune quarry, is part of the north-eastern massifs of the Constantine neritic series [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To identify groundwater potential zones, some studies have combined the GIS and RS with the multicriteria decision-making (MCDM) models (Saaty 2008;Aneesh and Deka 2015;Singh et al 2018;Maize et al, 2020). A few of them are the fuzzy logic (Mallick et al 2019), certainty factor (CF) (Razandi et al 2015), weighted overlay index (Prasad et al 2008), probabilistic models such as frequency ratio (FR) (Thapa et al 2017;Das and Pardeshi 2018;Braham et al 2022), multi-influencing factor (MIF) (Acharya et al 2019); machine learning (Saha et al 2022), and analytical hierarchy process (AHP) (Agarwal et al 2013;Ajay Kumar et al 2020;Arshad et al 2022;Aissaoui et al 2023). It is found that the use of the AHP model via GIS is an efficient and effective technique for the spatial data management, and also utilized to identify groundwater potential zones.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, Aissaoui et al (2023) in their study propose a methodology to identify the most suitable areas for groundwater recharge in the Middle Seybouse subcatchment in Guelma, North-East Algeria. They produced a map showing 60% of the investigated area has very high potential aquifer recharge and used receiver operating characteristic curve to validate it.…”
mentioning
confidence: 99%